Earlier corticosteroid use for adverse event management in patients receiving axicabtagene ciloleucel for large B‐cell lymphoma. (29th September 2021) - Topp, Max S.; van Meerten, Tom; Houot, Roch; Minnema, Monique C.; Bouabdallah, Krimo; Lugtenburg, Pieternella J.; Thieblemont, Catherine; Wermke, Martin; Song, Kevin W.; Avivi, Irit; Kuruvilla, John; Dührsen, Ulrich; et al.
Summary: Axicabtagene ciloleucel (axi‐cel) is an autologous anti‐CD19 chimeric antigen receptor (CAR) T‐cell therapy approved for relapsed or refractory large B‐cell lymphoma (R/R LBCL). To reduce axi‐cel–related toxicity, several exploratory safety management cohorts were added to ZUMA‐1 (NCT02348216), the pivotal phase 1/2 study of axi‐cel in refractory LBCL. Cohort 4 evaluated the rates and severity of cytokine release syndrome (CRS) and neurologic events (NEs) with earlier corticosteroid and tocilizumab use. Primary endpoints were incidence and severity of CRS and NEs. Patients received 2 × 10 6 anti‐CD19 CAR T cells/kg after conditioning chemotherapy. Forty‐one patients received axi‐cel. Incidences of any‐grade CRS and NEs were 93% and 61%, respectively (grade ≥ 3, 2% and 17%). There was no grade 4 or 5 CRS or NE. Despite earlier dosing, the cumulative cortisone‐equivalent corticosteroid dose in patients requiring corticosteroid therapy was lower than that reported in the pivotal ZUMA‐1 cohorts. With a median follow‐up of 14·8 months, objective and complete response rates were 73% and 51%, respectively, and 51% of treated patients were in ongoing response. Earlier and measured use of corticosteroids and/or tocilizumab has the potential to reduce the incidence of grade ≥ 3 CRS and NEs in patients with R/R LBCL receiving axi‐cel.